Empowering Tourism Awareness Group Based on Sapta Pesona Concept to Actualize Agro-Tourism Villages in West Bangka - Arif, Maulana; Haiyudi, Haiyudi; Teu, Teng (Universitas Ahmad Dahlan, 2023)
Background: To be financially independent village seems to be a must to support the local economic freedom. Tourism becomes one among some promising sectors. However, the low level of local understanding towards the concept of agro-tourism is much needed to support the local government development, especially in Tebing Village, West Bangka. Contribution: The purpose of this program is to support the actualization of an agro-tourism village based on green rice fields through the formation of a tourism awareness group and counseling on the concept, role and function of it in Tebing village, Sub-district of Kelapa, West Bangka Regency. Method: The method employed is by assisting, mapping and giving a lecture on the concept of tourism awareness groups to actualize the agro-tourism village in Tebing Village, West Bangka. Results: The result is proved by the formation of a tourism awareness group (Pokdarwis) in Tebing village. Besides, the growth of awareness and understanding related to the Sapta Pesona was well comprehend as qualitatively evaluated by interviewing the community. Finally, the mapping process of the location of agro-tourism was done using DJI Phantom 4 Pro. Conclusion: Existing natural resources can be utilized to increase income financially through agro-tourism villages. In addition, the happiness index can also be increased by the presence of green open space or agro-tourism nearby as a rest area from Pangkalpinang to Muntok or vice versa, as the village is located in the main route of it. Finally, this service still requires further assistance until the agro-tourism village can be established and support the village's independent income and the welfare of the local community